Unmanned aerial vehicles in logistics: foreign and domestic experience - E. S. Lunina; I. A. Ermakov (Вестник университета)
This article reviews and compares the experience of foreign and Russian companies using unmanned aerial vehicles (hereinafter referred to as UAV, drone) in the logistics industry. SWOT-analysis (strengths, weaknesses, opportunities, threats) is conducted which identifies strengths and weaknesses, opportunities and threats of using drones. Moreover, due to the current exi stence of a large number of prohibitions and restrictions on the application of this technology, the challenges of using drones in logistics are indicated. With the help of drones, companies are able to reduce costs and the likelihood of human error in work and thus increase efficiency by automating processes. These devices can optimise the process and improve logistics operations in a company. UAVs are the future not only of logistics but also of the technology industry as a whole. With the increasing scale of activity, each company tries to find and create new technologies that attract consumers and make its work more unique. The introduction of UAVs may become the means by which organisations can not only improve their activities by optimising and modernising processes, but also increase the visibility and scale of this performance.